Subsidiary Characters in Select William Gilletteâ€™s Play - Aaradhana, .; Dwivedi, Amitabh V. (Beyond Words, 2018)
Contemporary literature and recent media studies have taken so much from the genre called â€œSensational Novelsâ€, that even though this genre emerged in the late nineteenth century, it became hugely popular in the twentieth century, and also drew the attention of the present generation. The Detective fiction first presented to the world by Wilkie Collins, was introduced during the time when the concept and performance of the great detective and the sensation genre was blooming. One such work which became popular during that time was the narrative by Sir Arthur Conan Doyle centering on Sherlock Holmes. The aim of this paper is to examine the intriguing characters which Sir Arthur Conan Doyle and William Gillette constructed in the play of Sherlock Holmes. This consultant detective laid its impact on the readers in the nineteenth century, when it was first published, but even in the present times it had not lost its charms. The character of Sherlock Holmes became a sensational figure, due to which it had been the center of research by the scholars; however, the minor characters were studied seldomly. The paper with the help of Narratology, seeks to examine the William Gilletteâ€™s play; wherein, to show that the minor characters are essential for the development of the main protagonist, the narrative of the subsidiary characters will be analysed.